Cultura de paz : una construcción desde la educación - Hernández Arteaga, Isabel; Luna Hernández, José Alberto; Cadena Chala, Martha Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 149-172.